Seleção e caracterização molecular de cepas de Bacillus thuringiensis para controle do pulgão-verde-dos-cereais (Schizaphis graminum) - Moreira, Raquel Oliveira (2018)
Greenbug is a sap-sucking insect that infects crops causing damages not only as a direct result of feeding but also by their importance as vectors of plant viruses.S. graminumis considered a secondary pest of maize, but with an intensification of the pest management, especially for Lepidoptera order, it has been observed a recurrent infestation due to the reduced use of the broad-spectrum pesticides and the lack of intraspecific competition. So, the present work aimed to evaluate the molecular genetic profile of Bacillus thuringiensis (Bt) strains and its entomopathogenic potential for S. graminum.Bioassays against S. graminum were carried out using four elite strains entomopathogenic for pests of different orders and belonging to the collection of Microorganisms of Embrapa Maize and Sorghum. Furthermore, the expression of cry genes and protein profile analysis were also conducted for each strain.Strains 1644 and 1648 showed a higher and faster pathogenic effect, reducing insect survival rates to 20% after 48h and to 6% and 0%after 96h of exposure, respectively. The strains 1636 and 1641 were also entomopathogenic, but survival rates diminish more slowly. No expression of cry genes evaluated could be detected in 1644 and 1648 strains whereas the cry2Ab gene showed an expression profile characteristic of the sporulation-dependent cry genes. Total protein analysis from 1636, 1641 and 1644 strains showed different protein profiles with molecular weights ranging from 20 to 210 kDa. We could not associate proteins from 1644 and 1648 with Cry proteins. However, in the profile showed by 1636 strain, two bands with 60 and 130 kDa are similar to the Cry2A (70 kDa) and Cry1Ac (120 kDa) proteins, respectively. The results demonstrate the potential of these strains as a source of genes against S. graminum, besides evidencing the need to better understand the regulation of the cry genes in these isolates and to optimize the processes for obtaining products based onB. thuringiensis.